IMPLEMENTATION OF LICENSE TO ESTABLISH BUILDING (IMB) IN SOLOK CITY - Yusyaf, Noviandi; Faniyah, Iyah (UNES Journal of Swara Justisia, 2020)
Building is one of the needs for the community. With the increasing number of population and the increasingly narrow land, the need for control by the local government of the building. Solok City Regional Regulation No. 12 of 2003 concerning Building Permits confirms that a building permit is a permit to construct a building which includes building layout and design research activities, supervision of the construction. The approach that will be used in this research is a normative juridical approach and supported by empirical juridical. The data used are secondary data supported by primary data collected through library studies and field studies. The data was analyzed qualitatively and presented in a qualitative descriptive form. Based on the results of research and analysis it can be seen that: 1) the implementation of the granting of building permits in the City of Solok must go through procedures established by the government, which are required to attach documents and requirements relating to the management of building permits (IMB) which are then carried out by the relevant agencies RT / RW, Kelurahan, Camat and the One-Stop Integrated Investment and Services Office (DPMPTSP) 2) supervision of the city of Solok government in granting permits to build buildings is through administrative supervision and field supervision namely the survey of the location of building construction 3) constraints faced in granting permits constructing buildings is the lack of public understanding of IMB procedures and timeframe and there are still third party claims, and erecting buildings on public facilities.